2011
DOI: 10.3855/jidc.2242
|View full text |Cite
|
Sign up to set email alerts
|

Bangladeshi backyard poultry raisers’ perceptions and practices related to zoonotic transmission of avian influenza

Abstract: Introduction: Highly pathogenic avian influenza (H5N1) virus (known as "bird flu") is an important public health concern due to its potential to infect humans and cause a human pandemic. Bangladesh is a high-risk country for an influenza pandemic because of its dense human population, widespread backyard poultry raising, and endemic H5N1 infection in poultry. Understanding poultry raisers' perceived risks and identifying their risk exposures can help to develop interventions to reduce the risk of avian influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 23 publications
5
72
1
Order By: Relevance
“…Throwing dead poultry in bushes or water body is a common practice revealed in the present study which is in agreement with an inland report in which it has been reported that 85% respondents threw the offal or carcass either in bushes or nearest water body (Sultana et al, 2011).This study found a statistically significant relationship between knowledge and practices. Proper knowledge helped to create awareness and this leaded to good practices.…”
Section: Results and Discussion Socio-demographic Characteristics Of supporting
confidence: 82%
See 2 more Smart Citations
“…Throwing dead poultry in bushes or water body is a common practice revealed in the present study which is in agreement with an inland report in which it has been reported that 85% respondents threw the offal or carcass either in bushes or nearest water body (Sultana et al, 2011).This study found a statistically significant relationship between knowledge and practices. Proper knowledge helped to create awareness and this leaded to good practices.…”
Section: Results and Discussion Socio-demographic Characteristics Of supporting
confidence: 82%
“…Illiteracy is the main factor which hinders the awareness regarding to AI (Giuseppe et al, 2008). The findings about the respondents heard about AI differ from a previous survey conducted in Bangladesh, where 40% and 10% respondents from Rajshahi and Netrokona had heard about AI respectively (Sultana et al, 2011). Another study conducted among the live bird market workers in Mymensingh district had better percentage of respondents who had heard about AI; 83% in urban and 76% in periurban areas respectively (Sarker et al, 2009), the dissimilarity may be due to the study was conducted in backyard poultry raisers and live bird market workers respectively.…”
Section: Results and Discussion Socio-demographic Characteristics Of contrasting
confidence: 55%
See 1 more Smart Citation
“…Several people reported to sleep in the same room as their animals. Although this practice does not increase the risk of person-to-person spread of diseases among humans, it entails an increased risk for the spread of zoonoses, of which outbreaks are regularly reported from Bangladesh, for example, bovine tuberculosis, anthrax, avian influenza, or Nipah virus (33-35). …”
Section: Discussionmentioning
confidence: 99%
“…The European Food Safety Authority reserves its rights, view and position as regards the issues addressed and the conclusions reached in the present document, without prejudice to the rights of the authors. (Sheff, 2006) Study population Territory ) Territory (Shoji et al, 2009) Not relevant outcomes (Siddique et al, 2012) Territory (Siembieda et al, 2010) Not relevant outcomes (Simulundu et al, 2011) Territory (Simulundu et al, 2009) Territory (Sitaras et al, 2014) Not relevant outcomes (Skowronski et al, 2007) Study population (Slomka et al, 2007) Not relevant outcomes (Slomka et al, 2009) Not relevant outcomes (Slusher et al, 2014) Not relevant outcomes (Smietanka et al, 2005) Language Study population (Sonnberg et al, 2012) Territory (Spackman and Pantin-Jackwood, 2014) Not relevant outcomes ) Territory ) Territory (Stachyra et al, 2014) Not relevant outcomes (Stallknecht et al, 2010) Not relevant outcomes Not relevant outcomes (Steensels et al, 2009) Not relevant outcomes (Stegeman et al, 2004) Time interval (Suarez Fernandez, 2009) Language (Suárez Fernández, 2009) Language (Suarez et al, 2006) Territory (Suarez, 2005) Not relevant outcomes (Suenaga and Kumar, 2014) Not relevant outcomes (Sultana et al, 2012) Territory (Sun et al, 2011a) Not relevant outcomes (Sun et al, 2011b) Not relevant outcomes (Sun et al, 2014) Study population The present document has been produced and adopted by the bodies identified above as authors. This task has been carried out exclusively by the authors in the context of a contract between the European Food Safety Authority and the authors, awarded following a tender procedure.…”
Section: Citation Reason Of Exclusionmentioning
confidence: 99%